Employee Productivity: Work Environment, Job Satisfaction, Compensation in Covid-19 Pandemic: Dampak Lingkungan Kerja, Kepuasan Kerja, dan Kompensasi terhadap Produktivitas Karyawan selama Pandemi Covid-19 - Vira Fitria Januar Asifah Ahmad; Detak Prapanca (Academia Open, 2024)
This study aimed to investigate the impact of work environment, job satisfaction, and compensation on employee productivity during the Covid-19 pandemic at PT. Fajar Putra Plasindo. The study used a quantitative approach with a sample of 40 production employees. The data were analyzed using multiple linear regression analysis with SPSS Statistics version 22. The results showed that work environment, job satisfaction, and compensation had a significant effect on employee productivity. This study implies that companies should pay attention to work environment, job satisfaction, and compensation to increase employee productivity during the Covid-19 pandemic.Highlights: The study aimed to investigate the impact of work environment, job satisfaction, and compensation on employee productivity during the Covid-19 pandemic. The study used a quantitative approach with a sample of 40 production employees and analyzed the data using multiple linear regression analysis with SPSS Statistics version 22. The results showed that work environment, job satisfaction, and compensation had a significant effect on employee productivity. This implies that companies should pay attention to these factors to increase employee productivity during the Covid-19 pandemic. Keywords: Work environment, Job satisfaction, Compensation, Employee productivity, Covid-19 pandemi